OMNICHROMA – The revolutionary composite in the modern era - Bharath Makonahalli Jaganath; Sandeep Rudranaik; Sahadev Chickmagarvalli Krishnegowda; K. B. Nirmala; Yoganatha Hanasoge Nagashetty (Journal of Oral Research and Review)
Structurally colored resin composites have recently been developed to address the drawbacks of conventional composites. These composites feature a strong adhesion between the filler and base resin, providing excellent resistance to discoloration. Esthetic dentistry has significantly advanced in the 20th and 21st centuries, with OMNICHROMA, a new tooth-colored composite introduced by Tokuyama, representing a notable innovation. This article examines OMNICHROMA’s potential to revolutionize esthetic dentistry compared to conventional resin composites.